PENGARUH PEMBERIAN WALKING ON THE SPOT EXERCISE TERHADAP PENINGKATAN KEBUGARAN FISIK PADA PENDERITA HIPERTENSI DI KELOMPOK LANSIA PUSKESMAS SANDEN BANTUL - Nurhayati, Ummy A'isyah (Journal of Health Service Management, 2025)
Background: Elderly is a term used to describe people who undergo biological, physical and social changes as they age. Hypertension has become a common health problem in Indonesia. In Bantul Regency in 2020, there were 83,932 cases of hypertension from the total population. Walking is a form of low- to moderate-intensity aerobic exercise that most people can do easily and with minimal risk. Walking can improve cardiorespiratory fitness, muscle strength and body composition in older people. By measuring the 6MWT, a fitness level can be obtained which becomes a database for determining exercise programmes and interventions that are appropriate to the cardiorespiratory capacity of elderly hypertensive patients. Objectives: This study investigates the impact of walking on the spot exercise, on enhancing physical fitness in hypertensive patients in the elderly group of Puskesmas Sanden Bantul. Methods: Experimental research with a group pretest-posttest design. The sampling technique was purposive sampling. The number of samples is 30 people who are members of "Simbah Bugar" community who will be given walking on the spot exercise treatment. Normality test was conducted using Saphiro-Wilk test and hypothesis testing using Paired Sample T-test to determine the improvement in physical fitness from the treatment given. Results: The results of processing VO2 max values before and after treatment in testing the hypothesis of walking on the spot exercise using paired sample t-test obtained a value of p = 0.00. Before treatment, the mean VO2 max result was 13.38 and after treatment, the mean VO2 max result was 14.54 when measuring VO2 max using the 6MWT. Therefore, it can be concluded that the elderly group "Simbah Bugar" at the Sanden Bantul Health Centre has an effect on increasing the VO2 max by giving walking exercises on the spot. Conclusions: Walking on the spot may improve VO2 max in elderly hypertensive patients because it can improve respiratory function and oxygen transport.